2005
DOI: 10.1111/j.1365-2125.2005.02343.x
|View full text |Cite
|
Sign up to set email alerts
|

Diltiazem inhibits human intestinal cytochrome P450 3A (CYP3A) activity in vivo without altering the expression of intestinal mRNA or protein

Abstract: Br J Clin Pharmacol AimsTo determine the effect of diltiazem on intestinal CYP3A activity and protein and mRNA expression in vivo in healthy subjects. MethodsIntestinal biopsies were obtained from ten healthy controls and from ten healthy subjects after receiving diltiazem 120 mg bid for 7 days. Intestinal CYP3A activity, CYP3A4 protein and mRNA concentrations were quantified in both groups. Intestinal CYP3A activity was determined by incubation of small bowel homogenate with midazolam (25 m M) and NADPH for 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…In contrast to assuming F G Ј ϭ 1, the assumption that diltiazem reduces intestinal CYP3A4 activity by 62% (assessed by midazolam 1Ј-hydroxylation; Pinto et al, 2005) reduced this ratio and the extent of overpredictions, mainly for cyclosporine and buspirone interactions, respectively, by 54 to 190%; however, the predictions were still outside the 2-fold limits of in vivo values, in particular, for cyclosporine.…”
Section: Galetin Et Almentioning
confidence: 68%
“…In contrast to assuming F G Ј ϭ 1, the assumption that diltiazem reduces intestinal CYP3A4 activity by 62% (assessed by midazolam 1Ј-hydroxylation; Pinto et al, 2005) reduced this ratio and the extent of overpredictions, mainly for cyclosporine and buspirone interactions, respectively, by 54 to 190%; however, the predictions were still outside the 2-fold limits of in vivo values, in particular, for cyclosporine.…”
Section: Galetin Et Almentioning
confidence: 68%
“…Closed circles in A are observed DTZ concentrations on day 1 and day 6 of DTZ treatment (Lefebvre et al, 1994). Closed circle with error bar in B is observed CYP3A4 activity on the morning of the 8th day (Pinto et al, 2005). metabolites that would otherwise be difficult to identify. With the additive model incorporated into the semi-PBPK model for the simultaneous inactivation by DTZ and nd-DTZ, the -fold increase of MDZ AUC after oral and intravenous administration was accurately predicted.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutically important interactions between oral diltiazem and midazolam (MDZ) (Backman et al, 1994), triazolam (Varhe et al, 1996), cyclosporine (Wagner et al, 1988), lovastatin (Azie et al, 1998;Masica et al, 2000), and carbamazepine (Brodie and MacPhee, 1986;Eimer and Carter, 1987) have been documented. A previous study by our group also demonstrated that DTZ (120 mg twice daily for 7 days) caused a 62% decrease in small bowel CYP3A4 activity (Pinto et al, 2005). Thus, irreversible inhibition of CYP3A by DTZ is the most likely explanation for the nonlinear pharmacokinetics of DTZ.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…On the basis of in vitro models, clarithromycin was predicted to cause a reduction in the steady-state concentration of liver CYP3A4 to approximately 39% of the initial level (21). The mechanism of this autoinhibition was reported to be reversible (16,26), irreversible (2,15,25), and mediated by suicide inhibition by the formation of a metabolic intermediate complex (21). For clarithromycin, the ratio of the area under the free plasma concentration-time curve (fAUC) to the MIC is considered to be the most predictive pharmacokinetic-pharmacodynamic index (9,32) and is used to link the pharmacokinetic parameters to the most important antimicrobial pharmacodynamic parameter, i.e., the MIC.…”
mentioning
confidence: 99%